Identification and differential analysis of noncoding RNAs in response to drought in Phyllostachys aureosulcata f. spectabilis - Yang, Yang; Gao, Yuanmeng; Li, Yiqian; Li, Xueping (Frontiers in Plant Science, 2022)
The role of noncoding RNAs (ncRNAs) in plant resistance to abiotic stresses is increasingly being discovered. Drought stress is one of the most common stresses that affecting plant growth, and high intensity drought has a significant impact on the normal growth of plants. In this study, a high-throughput sequencing was performed on plant tissue samples of Phyllostachys aureosulcata f. spectabilis C. D. Chu et C. S. Chao by drought treatment for 0, 2, 4 and 6 days. The sequencing results were analysed bioinformatically. We detected 336,946 RNAs among all 12 samples, including 192,098 message RNAs (mRNAs), 142,761 long noncoding RNAs (lncRNAs), 1,670 circular RNAs (circRNAs), and 417 microRNAs (miRNAs). We detected 2,419 differentially expressed (DE) ncRNAs, including 213 DE circRNAs, 2,088 DE lncRNAs and 118 DE miRNAs. Then, we used Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) to functionally predict DE ncRNAs. The results showed that most DE ncRNAs are involved in the response to drought stress, mainly in biochemical reactions involved in some metabolites, as well as in organelle activities. In addition, we validated two random circRNAs and demonstrated their circularity. We also found a stable internal reference gene available for Phyllostachys aureosulcata f. spectabilis and validated the accuracy of this experiment by quantitative real-time polymerase chain reaction (qRT-PCR).